Colistin Resistance among Multi-Drug Resistant Gram-Negative Bacteria in Iran: A Systematic Review and Meta-Analysis - Fahimeh Hadavand; Fatemeh Khelghati; Arash Seifi; Shirin Afhami; Negin Esmailpour; Mahbobeh Alizadeh; Pardis Moradnejad; Fatemeh Nasirpour Seilakhori; Mohammad Javad Nasiri (Novelty in Biomedicine)
Background: Colistin, a last-resort antibiotic, faces a growing threat from antibiotic resistance. This study aims to comprehensively assess colistin resistance in clinical isolates of Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and Klebsiella pneumoniae in Iran.